Facile Solvothermal Synthesis of Hollow BiOBr Submicrospheres with Enhanced Visible-Light-Responsive Photocatalytic Performance - Linrui Hou; Yawei Niu; Fan Yang; Fengyue Ge; Changzhou Yuan (Journal of Analytical Methods in Chemistry)
In this work, hierarchical hollow BiOBr submicrospheres (HBSMs) were successfully prepared via a facile yet efficient solvothermal strategy. Remarkable effects of solvents upon the crystallinities, morphologies, and microstructures of the BiOBr products were systematically investigated, which revealed that the glycerol/isopropanol volumetric ratio played a significant role in the formation of hollow architecture. Accordingly, the underlying formation mechanism of the hollow submicrospheres was tentatively put forward here. Furthermore, the photocatalytic activities of the resulting HBSMs were evaluated in detail with photocatalytic degradation of the organic methyl orange under visible light irradiation. Encouragingly, the as-obtained HBSMs with striking recyclability demonstrated excellent visible-light-responsive photocatalytic performance, which benefits from their large surface area, effective visible light absorption, and unique hollow feature, highlighting their promising commercial application in waste water treatment.